Efficacy of lumen-apposing metal stents or self-expandable metal stents for endoscopic ultrasound-guided choledochoduodenostomy: a systematic review and meta-analysis - Amato, Arnaldo; Sinagra, Emanuele; Celsa, Ciro; Enea, Marco; Buda, Andrea; Vieceli, Filippo; Scaramella, Lucia; Belletrutti, Paul; Fugazza, Alessandro; Cammà, Calogero; Radaelli, Franco; Repici, Alessandro; Anderloni, Andrea (Endoscopy, 2021)
Background Endoscopic ultrasound (EUS)-guided biliary drainage is becoming an option for palliation of malignant biliary obstruction. Lumen-apposing metal stents (LAMS) are replacing self-expandable metal stents (SEMS). The aim of this meta-analysis was to evaluate the efficacy and safety of LAMS and SEMS for EUS-guided choledochoduodenostomy (EUS-CDS).Methods A meta-analysis was performed using PRISMA protocols. Electronic databases were searched for studies on EUS-CDS. The primary outcome was clinical success. Secondary outcomes were technical success, reintervention, and adverse events. We used the random effects model with the DerSimonian–Laird estimation, and the results were depicted using forest plots. Subgroup analyses were also performed with data stratified by selected variable.Results Overall, 31 studies (820 patients) were included. The pooled rates of clinical and technical success were 93.6 % (95 % confidence interval [CI] 88.6 %–96.5 %) and 94.8 % (95 %CI 90.2 %–97.3 %) for LAMS, and 91.7 % (95 %CI 88.1 %–94.2 %) and 92.7 % (95 %CI 89.9 %–94.9 %) for SEMS, respectively. The pooled rates of adverse events were 17.1 % (95 %CI 12.5 %–22.8 %) for LAMS and 18.3 % (95 %CI 14.3 %–23.0 %) for SEMS. The pooled rates of reintervention were 10.9 % (95 %CI 7.7 %–15.3 %) for LAMS and 13.9 % (95 %CI 9.6 %–19.7 %) for SEMS. Subgroup analyses confirmed these results.Conclusions This meta-analysis showed that LAMS and SEMS are comparable in terms of efficacy for EUS-CDS. Clinical and technical success, post-procedure adverse events, and reintervention rates were similar between LAMS and SEMS use; however, adverse events require further investigation.